The Correlation between Foreign Language Anxiety and Students' Speaking Performance - Rofida, Alfi (RETAIN, 2021)
Abstract Fear of speaking experienced by students when learning foreign language may be categorized as anxiety. Students’ fear of speaking may hamper their speaking performance. This study was a quantitative research that was conducted toi know the correlation between foreign language anxiety and students’ speaking performance. The instruments of this research were Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire that was adapted from Horwitz et al., (1986) and speaking rubric score that was adapted from Brown and Abeywickrama (2010). The data of this research were collected online with 50 participants from one of senior high school in Gresik. This research found that the students’ mostly experienced communication apprehension (M = 3.4) and fear of negative evaluation (M = 3.4) rather than test anxiety (M = 3.1). This research also showed that foreign language anxiety has significant negative correlation with students’ speaking performance (p = 0.000, r = -0.98) and the correlation strength was categorized as very strong. The higher level of students’ foreign language anxiety, the worse their speaking performance. Keywords: foreign language anxiety, speaking, speaking performance.